Le développement du photovoltaïque sur des terres agricoles, entre régulations publiques et jeux d'acteurs - Ronan Le Velly; Françoise Jarrige (VertigO, 2023)
The development of photovoltaic systems on agricultural land in France is still largely undocumented, and this article offers a contribution to understand the underlying mechanisms. The authors explain how this development takes place at the crossroads of national public regulation, public and private actors’ strategies and emerging territorial dynamics. They explain that the rules governing land use and renewable energy production constrain, but do not prohibit photovoltaics on agricultural land. They identify a priority rule for installation on artificial areas, but also four exceptions to the rule, all subject to interpretation processes. They then describe the strategies implemented in this context by agricultural actors, public authorities and energy companies. At local scales, energy companies seek out agricultural land, taking into account the doctrines asserted by local public authorities and professional agricultural organizations. On a national scale, these companies plead for the evolution of the game’s rules, partly to restrict the regulatory obstacles to photovoltaic installations on agricultural land, partly to gain recognition for approaches that they present as demanding in their combination of agriculture and energy production.